Analisis Rubrik Penilaian Biografi pada RPP Bahasa Indonesia - Muhammad, Khairani; Mukhlis, Muhammad (UIR PRESS, 2021)
This research is motivated by the number of teachers at SMA N 3 Mandau who made assessment rubrics. The problems studied in this study are: How is the analytical biographical assessment rubric in Indonesian RPP class X semester 2 of 2019/2020 SMA N 3 Mandau? What is the biographical holistic assessment rubric in Indonesian RPP class X semester 2 of 2019/2020 SMA Negeri 3 Mandau? The purpose of this study was to determine the rubric of biographical analytic assessment in Indonesian RPP class X semester 2 of 2019/2020 SMA Negeri 3 Mandau. To find out the biographical holistic assessment rubric in Indonesian RPP class X semester 2 of 2019/2020 SMA Negeri 3 Mandau. The research method used is the method of content analysis (Content Analysis). The research approach carried out by the author uses a qualitative research approach. The data collection technique in this research is documentation technique. The results of the research are the analytical rubric that the author obtained from the Indonesian RPP, which amounted to 6 data, not in accordance with the stages of designing a rubric which consists of 4 components, namely the criteria component, the weight component, the performance level component, and the score component. The holistic rubric that the author obtained from the Indonesian RPP consists of 4 data which are in accordance with the stages of designing a holistic rubric which consists of 2 components, namely the description component and the score component.